Community Aspirations on Making Regional Regulations in South Sumatra Province - Evi Oktarina (Journal of Governance, 2022)
The community attends public hearings or other gatherings to provide feedback or ideas; provides information to DPRD members during working visits; and attends seminars or similar events to conduct studies or follow up on various studies to develop a Draft Regional Regulation. During the planning, design, discussion, promulgation, and socialization stages of forming regional regulations, the community tends to close itself off from the regional government and Regional People's Representative Council, giving the impression that the community does not want to participate. Because they are not interested in the formation of local regulations, several strategies can be implemented to stimulate community participation, including consolidating the power of the community, especially stakeholders; empowering the community (building critical public awareness); publishing the results of essential investigations or research; trying to influence policymakers; generating action and continuous movement.